White oleander - Fitch, Janet (Warner Home Video, 2010)
Ingrid, a smart, free-spirited, and somewhat narcissistic artist kills her deceitful lover in a crime of passion. Even while serving a prison sentence, she exerts control over her adoring teenage daughter, Astrid, who's forced to spend her teenage years in a series of foster homes before becoming her own person. Explores the strange relationship of Ingrid and Astrid, and includes Astrid's relationship with her foster mothers. At first merely an appendage of her mother, Astrid develops as a result of her peripatetic adolescence.